2016
DOI: 10.1016/j.ypmed.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Educational attainment and the clustering of health-related behavior among U.S. young adults

Abstract: We documented health-related behavior clustering among US young adults and assessed the extent to which educational attainment was associated with the identified clusters. Using data from Wave IV of the National Longitudinal Study of Adolescent to Adult Health (Add Health), we performed latent class analysis on 8 health-related behaviors (n = 14,338), documenting clustering of behavior separately by gender. Subsequently, we used multinomial logistic regression and estimated associations between educational att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 36 publications
(42 reference statements)
11
49
0
4
Order By: Relevance
“…According to LMR p -values and relative changes in log-likelihood, BIC, and ABIC values, a three-cluster model was the most adequate fit of the data for both women and men, which is consistent with previous research on gender-specific health behavior clustering in the Add Health sample (Skalamera and Hummer 2016). Table 2 provides the fit statistics used to make this determination.…”
Section: Resultssupporting
confidence: 87%
“…According to LMR p -values and relative changes in log-likelihood, BIC, and ABIC values, a three-cluster model was the most adequate fit of the data for both women and men, which is consistent with previous research on gender-specific health behavior clustering in the Add Health sample (Skalamera and Hummer 2016). Table 2 provides the fit statistics used to make this determination.…”
Section: Resultssupporting
confidence: 87%
“…This is in contrast to the self-reports (Zajacova, Rogers & Johnson-Lawrence, 2012) and suggests that some of the sub-BA health penalty stemmed from differential reporting of health conditions by HS graduates versus those who attended college. However, our findings corroborate other studies where health returns to sub-baccalaureate education were modest or not significant (Skalamera & Hummer, 2016). …”
Section: Discussionsupporting
confidence: 91%
“…A recent study, however, found an intriguing anomaly: subbaccalaureate adults – who attended college but did not earn a bachelor's degree – reported more physical health problems and diagnoses than high school (HS) graduates who never attended college (Zajacova, Rogers, & Johnson-Lawrence, 2012). Several other studies also suggested that adults with “some college” did not always compare positively to HS graduates, for instance with respect to health behaviors (Rosenbaum, 2012; Skalamera & Hummer, 2016). This pattern is important because it contradicts the expectation that the college education beyond HS would yield health payoffs.…”
Section: Introductionmentioning
confidence: 96%
“…The higher risk for an alcoholexposed pregnancy among smokers might be associated, in part, with smokers being more likely to drink alcohol. Health risk behaviors including excessive alcohol use and cigarette smoking can co-occur (17). Incomplete data for analysis variables n = 132…”
Section: Conclusion and Commentsmentioning
confidence: 99%